On the Edge - Dashuk, Volha (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
The subject of “Europeanness” has been analysed in Belarus thoroughly for the last twenty years, but mainly in journalistic publications and books. It is hard to trace the implication of this topic in cinema. Nevertheless, a documentary examined from a certain angle can reveal a “European component”, manifesting important issues about Belarusian identity at the same time. The documentary We Are Living on the Edge (2002) by Victor Asliuk (Belarus) is reviewed in this connection. The reality shown in the film represents the European past and evokes a strong nostalgic feeling. However, the film, though generally renowned, is perceived differently by film professionals and audiences in Western and Eastern Europe. Some points of this East-West divergence are considered in the article. Finally, the issue of the relevance of Europe is analysed in the context of Belarusian history.